Pre-practice and pre-competition state anxiety among preadolescent female gymnasts: a pilot study - Reid, C.; Larson, A.; DeBeliso, M. (Journal of Physical Education Research, 2020)
An elevated state of cognitive and somatic anxiety may impede optimal sport performance. Identifying scenarios that may cause elevated levels of anxiety are salient such that appropriate anxiety management strategies can be employed. Gymnastics is a sport that may induce anxiety due to the nature of the apparatuses used, the potential for injury, and the competitive environment. The purpose of this study was to compare state anxiety in preadolescent female gymnasts prior to practice as well as a competition. Preadolescent female gymnasts (n=10) completed the Competitive State Anxiety Inventory-2 (CSAI-2) prior to two practice sessions and again prior to a competition. The CSAI-2 is comprised of three subscales (cognitive anxiety, somatic anxiety, and self-confidence). The CSAI-2 subscale scores were averaged for the two pre-practice sessions for comparison with the pre-competition condition. The CSAI-2 subscale scores were compared between the pre-practice and the pre-competition conditions with paired t-tests (a<0.05), -mean% scores, and effect size (ES) calculations. The CSAI-2 subscale score differences between the pre-practice and the pre-competition conditions approached statistical significance (cognitive anxiety p=0.10, somatic anxiety p=0.10, and self-confidence p=0.07). The CSAI-2 subscale score ES differences between the pre-practice and the pre-competition ranged from small to medium (cognitive anxiety ES=0.22, somatic anxiety ES=0.32, and self-confidence ES=-0.43). Within the parameters of this study, it appears that there is a decreased level of self-confidence and an increased level of anxiety prior to a competition when compared to a practice setting. These findings may hold practical value for coaches and gymnasts pursuing optimal performance.